Legal Status of Corporate Social Responsibility in GCC countries with special reference to Bahrain - Alhussein, Hussein Shhadah; Alenaze, Mohammed Saud Alnasair (Journal of Ecohumanism, 2024)
Earlier the concept of corporate social responsibility (CSR) was based upon philanthropic approach but now has become an imperative subject matter in the business world. Countries adopt different measures to implement CSR. In many countries, CSR is self-regulated voluntary activity like in Gulf cooperation countries. In Gulf countries the concept of Zakat Tax is equivalent to CSR. Though there is no legal mandate for CSR implementation in gulf countries still its filing and listing is mandatory. For the present study Doctrinal method is adopted by the researcher. The sources referred are primary as well as secondary for primary sources Statues and Government notifications and reports of the Committees are referred and in secondary sources newspaper reports, scholarly research articles are referred. The present paper is analytical in nature as it analyses the concept of CSR in consonance with other aspects such as legal mandate under Business law. It further aims to study the implications of mandating CSR. The present study is about CSR in GCC with special reference to Bahrain.